Preliminary Evaluation of Promising IRCT Glandless Cotton Varieties in Thailand - Guy Trebuil; Pipat Weerathaworn; Trung Bieu Nguyeni (Agriculture and Natural Resources, 1993)
Three recent varieties of glandless cotton from IRCT-CIRAD showed similar yields to the control Si Samrong 2 variety in an on-station productivity trial carried out during 1991 rainy season. An analysis of the agronomic, lint technology, yam technology and seed technology data obtained from this preliminary trial is presented. A tentative economic assessment of the benefits that such varieties could bring to the national ginning industry, subject to confirmation of these preliminary results by further crop protection studies and multilocation trials, is finally proposed. The ginning outturn of these glandless varieties was 3 to 4% higher than that of the control variety and they displayed better-quality lint, especially for length, uniformity, tenacity and maturity. When compared to Si Samrong 2, they also showed very significantly lower numbers of total neps and seed coat fragments. The three glandless varieties differ in fibre length, IRCT 413 being slightly longer than IRCT 411 (which has the highest ginning outturn); IRCT 412 is a long-fibre variety with high ginning outturn, but has more neps than the two other glandless cultivars.